Analisis Serangan dan Keamanan pada SQL Injection: Sebuah Review Sistematik - Tino Imam Maulana Pratama; Muhammad Danni Fawwas Songida; indra gunawan (Jurusan Informatika STTR Cepu, 2022)
The website is one of the most widely accessed information services by internet users in the world. As an information service, it is necessary to build a website that is able to handle requests from many users reliably. SQL Injection is a hacking action that is carried out in the client application by modifying the SQL commands that are in the client application memory and is a technique for exploiting web applications which use a database for data storage. SQL injection method is used to enter SQL commands as input on a website to gain access to the database. If the website database can be accessed, then a hacker can easily steal various confidential data, and can even manipulate or destroy data on the website.